Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." -- Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Homosexualités et tolérance sociale - Richard, Louis; Seguin, Marie-Thérèse; Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale (Éditions d'Acadie, 1988)
GRIIGES, Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale. Actes d'un colloque tenu du 9 au 11 oct. 1987 à l'Université de Moncton.
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; nouveau-brunswick; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Genre : une catégorie utile d'analyse historique - Scott, Joan (Les cahiers du GRIF, 1988)
Keywords: 1900-1999; cours; discipline; fem1000; genre; histoire; identités LGBTQIA2+; premier cycle; périodes historiques; ressource en ligne; sciences humaines; thématiques; théories féministes

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Le triangle rose : la déportation des homosexuels (1933-1945) - Boisson, Jean (Laffont, 1987)
Keywords: 1900-1999; LGBTQIA2+; allemagne; approches et analyses; camps de concentration; cours; discipline; discours dominant; europe; his4860; histoire; histoire de la sexualité; histoire et politique; holocauste; homophobie; homosexualité; hétérosexisme; identités LGBTQIA2+; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; sexualité; systèmes d'oppressions; thématiques

Geography of gender in the third world - Momsen, Janet Henshall; Townsend, Janet G. (University of New York Press, 1987)
This pioneering book addresses a key issue in development studies. It follows the influential 'Geography and Gender' as the second collaborative work generated by the Women in Geography Study Groups of the Institute of British Geographers. Its twenty substantive papers explore spatial patterns of gender in Asia, Africa, the caribbean and Latin America. The book's contributors come from Europe, North and South America, India, Sri Lanka, Malaysia, Thailand, Egypt and the Caribbean. 'Geography of Gender in the Third World' analyses the position of women and the societies that ignore and exploit them. it provides both substantial original research and a comprehensive introduction to the geography of gender in low income countries. The book makes a powerful claim for the regional geography of gender.
Keywords: 1900-1999; afrique; amériques; asie; cours; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sud global; thématiques

La lettre aérienne - Brossard, Nicole (Les éditions du remue-ménage, 1985)
Lieu d’invention, laboratoire où s’élaborent une pensée originale et la recherche d’un langage inédit, La lettre aérienne rassemble douze essais de Nicole Brossard écrits entre 1975 et 1985. Ces textes témoignent de la quête individuelle de l’écrivaine, ancrée dans l’histoire, dans l’affirmation de la modernité québécoise et l’émergence d’une culture affranchie de la norme patriarcale.
Keywords: amériques; approches et analyses; arts; cours; discipline; fem1000; identités; identités LGBTQIA2+; lesbianisme; lit3495; littérature; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Femme, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques